FORMATION OF THE COMMITMENT TO NATIONAL AND HUMAN VALUES IN CHILDREN AND YOUTH IS AN IMPORTANT PRIORITY OF THE ESSENTIAL LAW - Djavakova K (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  The  article  reveals  the  essence  and  importance  of  the  formation  of commitment among children and youth to national and universal values, analyzes the legal  conditions,  regulatory  legal  acts  adopted  in  Uzbekistan  and  devoted  to  the effectiveness  of  youth  policy.  The  article  considers  the  importance  of  patriotic education, which consolidates society and prevents the worst qualities in people from manifesting  themselves  -  indifference,  selfishness,  individualism,  cynicism, unmotivated aggression, disrespect for the state and its social institutions.